Influência da corrente de soldagem nas propriedades mecânicas de juntas soldadas de aço A36 - Morais, Márcio Diego de Oliveira (Universidade Federal Rural do Semi-Árido, 2019)
The present work has the objective to make an analytical study of the behavior of ASTM A36 steel submitted to different welding energies. In this work, three different electric current intensities will be used, with the values of 100, 150 and 200 amps (A) being presented, where welding of steel plates will be performed, serving as samples for more general cases. In order to carry out the study of the variation of the electric current (welding energy), some specimens were prepared and submitted to the tensile and microhardness tests, in order to obtain a better information on the behavior of a material (in this case, the steel A36) with equal dimensions when subjected to different electric current. The tensile and microhardness tests were carried out and conclusions were drawn on the collected data, where it was possible to perceive the parameters that underwent changes with the variation of the amount of heat supplied, including some mechanical properties that underwent changes
Monografia
Keywords: Aço ASTM A36; Corrente elétrica; Soldagem; Ensaios; ENGENHARIAS::ENGENHARIA MECANICA